Nutrition literacy in sports: exploring sport type-specific effect on ergogenic aids utilization - Khairunnisa, Prima Amanda; Isaura, Emyr Reisha; Sari, Diandra Puspita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Introduction: The role of nutrition in athletic performance is crucial. However, the nutritional requirements and literacy levels vary among athletes across different sports disciplines and influenced by various factors. Aims: This study investigates how nutrition literacy varies among athletes in different sports, exploring the factors, and examines the correlation between athletes' nutrition literacy levels and their use of ergogenic aids. Methods: This study employed a systematic literature review following the PRISMA method. Conducting searches across databases Scopus and PubMed using keywords including